Alfred North Whitehead correspondence - Whitehead, Alfred North, 1861-1947.
ALS (1936 January 10) from Whitehead to Henry Siggins Leonard in response to Leonard's essay, "Logical Positivism and Speculative Philosophy" (1936). Includes a typewritten transcript of the letter.
Mathematician and philosopher.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Leonard, Henry Siggins, -- 1905-1967 -- Correspondence; Logical positivism; Philosophy; Mathematicians; Philosophers